2011
DOI: 10.3390/en4122249
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Decomposition of Factors Affecting Energy-Related Carbon Emissions in Guangdong Province, China

Abstract: Abstract:Guangdong is China's largest province in terms of energy consumption. The energy-related carbon emissions in Guangdong province are calculated, and two extended and improved decomposition models for energy-related carbon emissions are established with the Logarithmic Mean Divisia Index method based on the basic principle of Kaya identity. Main results are as follows: (1) the energy-related carbon emissions from the three strata of industry, except the primary industry, and household energy consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 18 publications
(9 reference statements)
2
40
0
1
Order By: Relevance
“…Researchers have quantified the impact of different factors on the change of CO2 emissions from the regional [3][4][5][6] to the sectoral [7][8][9] perspective, and generally divided the factors into energy mix, energy intensity, industrial structure, economic activity, and population scale. Pani and Mukhopadhyay [3] undertook a decomposition study of CO2 emission of the top ten emitting countries and indicated that although rising income and population are the main driving forces, they are neither necessary nor sufficient for increasing emission, rather, energy structure and emission intensities are the crucial determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have quantified the impact of different factors on the change of CO2 emissions from the regional [3][4][5][6] to the sectoral [7][8][9] perspective, and generally divided the factors into energy mix, energy intensity, industrial structure, economic activity, and population scale. Pani and Mukhopadhyay [3] undertook a decomposition study of CO2 emission of the top ten emitting countries and indicated that although rising income and population are the main driving forces, they are neither necessary nor sufficient for increasing emission, rather, energy structure and emission intensities are the crucial determinants.…”
Section: Introductionmentioning
confidence: 99%
“… is the optimal β matrix for China, 2  for US, 3  for Russia, 4  for India and 5  for Japan. It could be found that the optimal β it values vary quite a lot from each other even for the same county.…”
Section: Experimental Simulationmentioning
confidence: 99%
“…Fossil fuel consumption, attributed to economic growth in a large part, comprises 80% of the World's energy use [2]. It is scientifically understood that the detrimental impacts of GHG emissions, especially carbon dioxide (CO 2 ) emissions, on the living environment such as global warming, greenhouse effect, and climate change are mainly the result of fossil fuel combustion for heat supply, electricity generation and transportation purposes [3]. About three quarters of the human-caused carbon emissions of the past 20 years derived from fossil fuel burning.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ANN, a large number of applications have shown that ANN can be a quite suitable tool within the stationary forecasting domain, predicting factors such as carbon emissions [21,22], construction costs [23], and stock market behavior [24]. ANN has been adopted to predict building cooling loads [25,26] and annual building energy consumption levels [19], given that energy consumption datasets are highly non-stationary as regards the relationship between input variables and the outputs of a complex system [26].…”
Section: Energy Consumption Modeling Researchesmentioning
confidence: 99%